Physical Appearance and Sexual Activity Mediate the Link Between Early Puberty and Sexual Harassment Victimization in Male Adolescents. - Skoog, Therése; Bayram Özdemir, Sevgi (Sex Roles, 2016)
Contrary to common belief, research shows that male adolescents are frequent targets of sexual harassment. According to some prior studies, early puberty puts male adolescents at a particular risk for being sexually harassed. In this cross-sectional study, we tested two competing explanations of the link between male pubertal timing and sexual harassment in early adolescence. The explanations were based on evolutionary and feminist theories. The sample included 704 seventh-grade Swedish male adolescents ( M = 13.37, SD = .59). We found that looking more mature and being sexually active significantly mediated the link between pubertal timing and sexual harassment. The magnitude of the indirect effects did not differ significantly from each other. These findings largely replicate prior research for female adolescents, and they suggest that early pubertal timing is linked to victimizing sexual phenomena in early adolescence through young men's normative sexually mature appearance and sexual activities. Tolerance and respect for differences should be central components of interventions aimed at reducing sexual harassment among young people of any gender.